2015
DOI: 10.1039/c5ta04527d
|View full text |Cite
|
Sign up to set email alerts
|

Na2.44Mn1.79(SO4)3: a new member of the alluaudite family of insertion compounds for sodium ion batteries

Abstract: Sodium-ion batteries have been extensively pursued as economic alternatives to Lithium-ion batteries. Investigating the polyanion chemistry, alluaudite structured Na 2 Fe II 2 (SO 4 ) 3 has been recently discovered as a 3.8 V positive electrode material (Barpanda et al, Nature Commun., 5:4358, 2014). Registering the highest ever Fe III /Fe II redox potential (vs. Na/Na + ) and formidable energy density, it has opened up a new polyanion family for sodium batteries. Exploring the alluaudite family, here we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 29 publications
0
68
1
1
Order By: Relevance
“…[ 185,186 ] The Mn-based alluaudite Na 2+2 x Mn 2-x (SO 4 ) 3 and solid-solution phase of Na 2.5 (Fe 1-y Mn y ) 1.75 (SO 4 ) 3 were also investigated as cathodes for NIBs. [187][188][189] However, these electrodes exhibited marginal electrochemical activities of Mn 2+ /Mn 3+ in Na-ion cells. Recent work introduced the new eldfellite-type NaFe(SO 4 ) 2 ; however, this electrode exhibited a low energy density with an average voltage of 3 V and specifi c capacity of 80 mA h g −1 .…”
Section: Fluorosulfates and Sulfatesmentioning
confidence: 99%
“…[ 185,186 ] The Mn-based alluaudite Na 2+2 x Mn 2-x (SO 4 ) 3 and solid-solution phase of Na 2.5 (Fe 1-y Mn y ) 1.75 (SO 4 ) 3 were also investigated as cathodes for NIBs. [187][188][189] However, these electrodes exhibited marginal electrochemical activities of Mn 2+ /Mn 3+ in Na-ion cells. Recent work introduced the new eldfellite-type NaFe(SO 4 ) 2 ; however, this electrode exhibited a low energy density with an average voltage of 3 V and specifi c capacity of 80 mA h g −1 .…”
Section: Fluorosulfates and Sulfatesmentioning
confidence: 99%
“…(Fig. 28 The bands at 620cm -1 , 998cm -1 and 1118cm -1 Please do not adjust margins Please do not adjust margins are attributed to asymmetric bending, symmetric and asymmetric stretching vibrations of SO 4 groups, respectively. The angle of Mn (2) the Mn 2+ doesn't get oxidized in the process of high temperature crystal growth.…”
Section: Structurementioning
confidence: 99%
“…28 Almost at the same time, Marinova et al also reported that Na 2+σ Mn 2-σ/2 (SO 4 ) 3 has electrochemical activity in the lithium ions cell. Na2+2xM2-x(SO4)3 (M=Fe and Mn), which can make the NIBs competitive with the state-of-the-art Li-ion batteries (LIBs).…”
mentioning
confidence: 94%
“…For example, Deng et al have reported a free-standing alluaudite Na 2+2x Fe 2−x (SO 4 ) 3 @ porous carbon-nanofiber hybrid film with a high rate capability of 40 C and long cyclic life over 500 cycles [106]. Some analogous sulfates, such as NaFe(SO 4 ) 2 [107] [109], were also reported, but the performances are not satisfying.…”
Section: Sulfatesmentioning
confidence: 99%